The impact of energy drinks on health of children and young adults - review of latest research - Kożuchowska, Klaudia; Pilarz, Dawid; Szewczyk, Marcelina; Morawska, Maria; Tomczyk, Aleksandra; Ufnal, Julia; Lewandowska, Dominika; Rosińska-Lewandoska, Dominika; Drewko, Klaudia; Jarosz, Kinga (Journal of Education, Health and Sport, 2025)
Introduction and purpose Consumption of energy drinks has become popular all over the world. Energy drinks are non-alcoholic beverages that contain large amounts of caffeine, sugar, and substances like vitamins, taurine, ginseng, creatine, and guarana. The aim of our research is to present the latest data on impact of energy drinks on health of children, adolescents, and young adults. Description of the state of knowledge Regular consumption of energy drinks is associated with numerous adverse health effects. The main areas of impact are the cardiovascular system and the nervous system. High concentrations of caffeine - the main ingredient in energy drinks can lead to increased heart rate, increased blood pressure and heart rhythm disorders. Consuming energy drinks leads to hypertension and increased cardiovascular risk. In addition, energy drinks can cause sleep disorders, anxiety and hyperactivity. Energy drinks are characterized by a high sugar content, which promotes obesity, type 2 diabetes and tooth decay. Materials and methods Systematic literature review was conducted using PubMed and Google Scholar databases to obtain most accurate and recent results. The key words included ,,energy drinks”, ,,children”, ,,health”,,cardiovascular system” and ,,caffeine.” Conclusions This review provides further evidence that consumption of energy drinks by children and adolescents is associated with many adverse effects for physical and mental health. Mainly predisposed systems are cardiovascular and nervous. Further research is needed, with emphasis on maintaining ethics, to determine long-term effects of Energy Drinks use in these populations.